The Role of the Family in the Formation of Islamic Character in Early Childhood (Case Study of the Coastal Community of Prenduan Village RT 005 RW 001) - Nailah Nabila; Fathorrahman Fathorrahman (STIT Attaqwa, 2026)
The family is the main and most important environment because it is tasked with laying the foundations of education in child development. The minimal role of the family in shaping the Islamic character of early childhood has an impact on children's behavior that is not in line with religious values. In this study. The researcher used a qualitative approach with a case study research type. The data collection method used here is through observation, interviews, and documentation. While the informants in this study are RT, RW, religious leaders / Koranic teachers, and parents in the coastal hamlet of Prenduan RT 005 RW 01. The issues raised here are about the role of the family in shaping children's Islamic character well, and the factors that influence the formation of Islamic character in children. The family has a very important role in shaping the Islamic character of children from an early age. Through direct education, providing examples, and getting used to worship from an early age, the family becomes the main environment for instilling Islamic values. The role of parents as examples of positive behavior and involvement in religious activities has a significant influence. Overall, the formation of Islamic character requires good cooperation between the role of the family, religious education, and a positive environment.